Filamin A Is a Potential Driver of Breast Cancer Metastasis via Regulation of MMP-1 - Zhou, Jie; Wu, Lvying; Xu, Pengyan; Li, Yue; Ji, Zhiliang; Kang, Xinmei (Frontiers in Oncology, 2022)
Recurrent metastasis is a major fatal cause of breast cancer. Regretfully, the driving force and the molecular beneath haven’t been fully illustrated yet. In this study, a cohort of breast cancer patients with locoregional metastasis were recruited. For them, we collected the matched samples of primary tumor and metastatic tumor, and then determined the mutation profiles with whole-exome sequencing (WES). On basis of the profiles, we identified a list of deleterious variants in eight susceptible genes. Of them, Filamin A (FLNA) was considered a potential driver gene of metastasis, low expression of which could enhance five years’ relapse survival rate by 15%. To prove the finding, we constructed a stable FLNA knockout tumor cell line, which manifested the cell abilities of proliferation, migration, and invasion were significantly weakened in response to the gene knockout. Subsequently, xenograft mouse experiments further proved that FLNA knockout could inhibit local or distal metastasis. Putting all the results together, we consolidated that FLNA could be a potential driver gene to metastasis of breast cancer, in particular triple-negative breast cancer. Additional experiments also suggested that FLNA might intervene metastasis via regulation of MMP-1 expression. In summary, this study demonstrates that FLNA may play as a positive regulator in cancer proliferation and recurrence. It provides a new insight into breast cancer metastasis and suggests a potential new therapeutic target for breast cancer therapy.